1929
DOI: 10.1084/jem.50.6.777
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactic Shock With the Partial Antigen of the Tubercle Bacillus

Abstract: 1. Typical lethal anaphylactic shock has been produced in guinea pigs by means of the specific carbohydrate derived from a human strain of tubercle bacillus. The phenomenon has been observed in animals both actively and passively sensitized. 2. Typical contractions have been evoked in the isolated uterus of guinea pigs upon the addition of the specific carbohydrate to the bath. 3. True anaphylactic shock against the specific carbohydrate in guinea pigs sensitized with the tubercle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1931
1931
1976
1976

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…The negative character of protein tests would indicate, however, that very little, if any, of the nitrogen is present as protein. The above results, furthermore, are in harmony with those of Tomcsik (12), Tomcsik and Kurotchkin (13), Lancefield (14), Avery and Tillett (15), and Enders (16), who found that bacterial carbohydrates, nitrogenfree in the case of Types II and III pneumococci, had the property of producing anaphylactic shock in guinea pigs passively sensitized with rabbit immune serums prepared against the corresponding organisms. Analogous results with monilia soluble substance are presented in the preceding paper (2).…”
Section: Discussionsupporting
confidence: 88%
“…The negative character of protein tests would indicate, however, that very little, if any, of the nitrogen is present as protein. The above results, furthermore, are in harmony with those of Tomcsik (12), Tomcsik and Kurotchkin (13), Lancefield (14), Avery and Tillett (15), and Enders (16), who found that bacterial carbohydrates, nitrogenfree in the case of Types II and III pneumococci, had the property of producing anaphylactic shock in guinea pigs passively sensitized with rabbit immune serums prepared against the corresponding organisms. Analogous results with monilia soluble substance are presented in the preceding paper (2).…”
Section: Discussionsupporting
confidence: 88%
“…Several authors have succeeded in performing passive transfer of sensitivity to guinea pigs with rabbit antibacterial serum, and in shocking them with the corresponding carbohydrates. In this respect the investigations of Avery and Tillett (1929) with pneumococci and of Enders (1929) with tubercle bacilli are especially interesting. In our work, passive sensitization permitted us to demonstrate in guinea pigs, and to some extent in mice, desensitization with small doses of NPD.…”
Section: Discussionmentioning
confidence: 96%
“…Some evidence has accumulated to suggest that this anaphylactic type response is elicited by tuberculopolysaccharide, whereas the delayed sensitivity pattern is caused by tuberculoprotein. Enders (17) found that, in guinea pigs actively or passively sensitized to tubercle bacilli, the tuberculopolysaccharide of Mueller (18) evoked positive Schultz-Dale reactions and anaphylaxis. On the other hand, a large body of evidence, well summarized by Drea and Andrejew (19), indicates that the delayed type of tuberculin reaction is in response to a protein material.…”
mentioning
confidence: 99%